Rediscovery and supplemental description of Begonia hymenophylloides (Begoniaceae) as new record in China - Tian, Jing; Wang, Yan; Ren, Jing; Peng, Shuai; Wang, Jun-Jie; Zhang, Cai-Fei; Hu, Guang-Wan (Phytotaxa, 2021)
N/A